2006
DOI: 10.1002/humu.9428
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of maple syrup urine disease in Spain

Abstract: Mutations in any of the three different genes BCKDHA, BCKDHB, and DBT encoding for the E1alpha, E1beta, and E2 catalytic components of the branched-chain alpha-ketoacid dehydrogenase (BCKD) complex can cause maple syrup urine disease (MSUD). The disease presents heterogeneous clinical and molecular phenotypes. Severity of the disease ranges from the classical to the mildest variant types. Here, we describe the MSUD genotypes and related phenotypes in a cohort of 33 Spanish patients. Based on complementation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 27 publications
6
40
1
4
Order By: Relevance
“…A total of 15 mutations were identified in BCKDHA, BCKDHB, and DBT genes in our MSUD patients. BCKDHB mutations were most common in neonates with the more severe classical form of MSUD in our study, which is in agreement with previous findings (21). However, other studies have reported contradictory findings: one study identified BCKDHB mutations in patients with the intermediate and thiamine-responsive forms of MSUD (22), while another observed BCKDHB mutations in patients with the intermittent or asymptomatic forms of MSUD (11).…”
Section: Discussionsupporting
confidence: 91%
“…A total of 15 mutations were identified in BCKDHA, BCKDHB, and DBT genes in our MSUD patients. BCKDHB mutations were most common in neonates with the more severe classical form of MSUD in our study, which is in agreement with previous findings (21). However, other studies have reported contradictory findings: one study identified BCKDHB mutations in patients with the intermediate and thiamine-responsive forms of MSUD (22), while another observed BCKDHB mutations in patients with the intermittent or asymptomatic forms of MSUD (11).…”
Section: Discussionsupporting
confidence: 91%
“…At least homozygous p.Gly290Arg and p.Val412Met were associated with very low (2-4%) residual BCKD activity in cultured fibroblasts. Thus, for the homoallelic p.Gly290Arg genotype the prediction of a severe variant MSUD phenotype with neonatal manifestation (Chuang et al 1995;Rodriguez-Pombo et al 2006) is verified. The same holds true for the previously described p.Ala253Thr mutation (Nobukuni et al 1993) and the p.Val412Met mutation (Henneke et al 2003) in the BCKDHA gene.…”
Section: Discussionmentioning
confidence: 87%
“…and two E1" subunits. The genomic changes that impair BCKD activity can occur in any of the catalytic components of the complex, but both alleles at a single gene locus must harbour nucleotide changes (Aevarsson et al 2000;Chuang and Shih 2001;Nellis and Danner 2001;Rodriguez-Pombo et al 2006). Based on the affected loci of the BCKD complex, three molecular MSUD genotypes are known so far: subtype Ia for mutations affecting the E1!…”
Section: Introductionmentioning
confidence: 99%
“…For example, intragenic deletion and duplication mutations had not been documented in MSUD patients previously. Molecular characterization of MSUD alleles has a ϳ95% mutation detection rate with a mutation spectrum of ϳ95% point mutations; the remaining 5% were considered uncharacterized mutations, 35,36 and large and single-exon deletions and duplications had not been seen before. Here we present for the first time two cases of multiexon deletion and duplication mutations in the BCKDHB gene, identified in patient T6 and T5, respectively.…”
Section: Discussionmentioning
confidence: 99%